Clinical Description and Diagnosis of HIV/AIDS - Suryono, Suryono; Nasronudin, Nasronudin (Institute of Topical Disease Universitas Airlangga, 2014)
Infections of HIV/AIDS currently has become very serious problems for the world health. In the country the first case of HIV/AIDS was discovered in Bali in 1987, in its progress has not the meaning but after 1985 HIV transmission increased considerably. The complex problem that the living and the increasing number of cases should indeed, medical practitioners understand more the clinical and how to diagnose infections of HIV/AIDS. A snapshot of the clinical HIV infection/aids can be seen from grievances and a diseasethat often accompanies it, a complaint which is found at HIV/AIDS sufferers in the form of suds retroviral acute: fever, weight loss, diarrhea chronic, disphagi, limpadenopati, infections in the skin respiratory disorders and nervous breakdown center. While a disease that often been gained by those with HIV / AIDS as candidiasis, tuberculosis, pneumonia bakterialis, toksoplasmosis and pneumonia pneumocystic carinii. Diagnose HIV infection created based on clinical symptoms which includes major symptoms and symptoms ofminor, and the result of the examination of the laboratory.